Uncovering the Power of Consumer Involvement: How Perceived Quality Drives E-Commerce Behavior? - Asyhari, Asyhari; Pudjihastuti, Sri Hindah; Alfionita, Vina; Othman, Azmahani Yaacob (Universitas Brawijaya, Indonesia, 2024)
Consumer involvement is an important factor in shaping consumer behavior, such as purchase intention, satisfaction, and loyalty. However, scholars have not explored its impact on e-commerce. This study aims to investigate the impact of consumer involvement, which consists of opinion-seeking, product variety, and product involvement, on perceived quality and e-commerce behavior. A quantitative research design uses 300 respondents from Oclo Official consumers in Semarang City. Data analysis using Partial Least Square Structural Equation Model (PLS-SEM) with SmartPLS version 4.0.9. The findings revealed that opining-seeking, product variety, and involvement have a positive effect on perceived quality. Other findings demonstrated that perceived quality has a positive effect on e-commerce behavior. Finally, the result concluded that perceived quality can mediate relationship factors in e-commerce behavior. The implication of this study offers new insights into the importance of consumer involvement in e-commerce. The most important implication is that e-commerce businesses must enhance perceived product quality, as it directly influences customer behavior, such as purchase intention, satisfaction, and loyalty. Companies can strengthen long-term relationships with consumers by offering a wider variety of products and maintaining high quality.